Temporal Trends of Transcatheter Edge-to-Edge Repair of the Mitral Valve Short-Term Outcomes in the United States: Nationwide Representative Study. Issue 3 (4th May 2021) - Abdelfattah, Omar M.; Saad, Anas M.; Hisung, Ingrid; Abushouk, Abdelrahman I.; Gad, Mohamed M.; Okasha, Osama; Isogai, Toshiaki; Ahuja, Keerat R.; Shekhar, Shashank; Burns, Daniel J. P.; Krishnaswamy, Amar; Kapadia, Samir R.
ABSTRACT: Background : Transcatheter edge-to-edge repair of the mitral valve (TEER) has recently emerged as a viable treatment option in high-risk patients with severe mitral regurgitation. The present study investigated the trends in TEER short-term outcomes during 2014–2018. Methods : We performed a retrospective study using the Nationwide Readmissions Database. We analyzed data on the in-hospital and 30-day outcomes of patients who underwent TEER procedure during 2014–2018. Results : A total of 22, 914 patients underwent TEER; 1, 674 in 2014, 3, 252 in 2015, 4, 645 in 2016, 6, 000 in 2017, and 7, 343 in 2018 with a median age of 78, 80, 81, and 80 years, respectively, with a 4.2 fold increase in TEER utilization. Heart failure was present in 75.6%, and 83.6% of patients, in 2014, and 2018 respectively, while 73.3%, and 85.3% of patients, respectively, had hypertension. In-hospital mortality following TEER was significantly decreased from 3.9% in 2014 to 2% in 2018 ( P < 0.001). Similarly, stroke rates were decreased from 1.2% in 2014 to 1% in 2018 ( P = 0.093), and the median length of hospital stay was significantly shortened from 4 to 2 days ( P < 0.001). The overall 30-day readmission rate was 15.3% and did not change significantly over the study period ( P = 0.876); however, the 30-day HF readmission rate exhibited a significant decline from 4.7% in 2014 to 0.6% in 2018 ( P < 0.001). Conclusion : Although TEER therapy is now offered to a more critically ill and larger patient population in the United States, the outcomes of patients undergoing TEER are improving with decreasing mortality, morbidity, and hospital stay. Abbreviations : TEER: Transcatheter edge-to-edge repair of the mitral valve (TEER); NRD: National Readmissions Database; MR: Mitral Regurgitation; DMR: Degenerative Mitral Regurgitation; FMR: Functional Mitral Regurgitation; HF: Heart failure; LVEF: Left Ventricular Ejection Fraction; GDMT: Guideline-Directed Management and Therapy; AKI: Acute Kidney Injury; MI: Myocardial infarction